Pengembangan Model Pelayanan Kebidanan Berbasis Komunitas untuk Meningkatkan Kesehatan Ibu dan Anak di Kota Kendari - Suhartati, Suhartati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Maternal and child health is an important indicator in assessing the quality of health services in a region. Kendari City, as one of the developing cities in Indonesia, faces challenges in providing equitable, affordable, and quality midwifery services to the community. This study aims to develop a community-based midwifery service model that can improve maternal and child health through promotive, preventive, curative, and rehabilitative approaches. The research method used was a qualitative study with a participatory approach, involving midwives, community leaders, health cadres, and pregnant and breastfeeding women as participants. Data were collected through in-depth interviews, focus group discussions (FGDs), and participant observation. The results indicate that community-based midwifery services can improve service accessibility, strengthen the role of health cadres, and raise public awareness of the importance of maternal and child health care. The resulting model emphasizes cross-sector collaboration, strengthening the role of families, and empowering communities as active partners in midwifery services. In conclusion, the development of a community-based midwifery service model is effective in improving the quality and equity of maternal and child health services in Kendari City.